Forgiveness Viewed from Positive Psychology and Islam: Array - Idi Warsah (Islamic Guidance and Counseling Journal, 2020)
Conflicts are unavoidable in human life. Thus, for human beings, the attitude of forgiveness is of importance to be well-embedded and sustainably constructed. Resting upon the aforesaid premises, the present study conducted a library research to reveal how forgiveness is viewed from the perspectives of positive psychology and Islam. 102 scientific works reviewed, 58 works were finally selected to be scrutinized in depth. This study revealed that the discourses in the field of positive psychology imply that forgiveness attitude is of importance to be embedded in human beings and continuously constructed by virtue of its positive natural impacts on mental health, good relationships, physical health, and positive well-being. Furthermore, as informed by Islamic teachings, the attitude of forgiveness is also suggested to be well and continuously embedded. As the best Islamic role model for the end-time people, the Prophet Muhammad PBUH already exemplified that humans are indeed to always be forgiving and even to pray for others for the sake of good things that Allah SWT will bestow to. It is worth noting that both positive psychology and Islam encourage humans to be forgiving individuals.